2016
DOI: 10.11114/ijsss.v4i5.1526
|View full text |Cite
|
Sign up to set email alerts
|

Power Relations Influencing Catholic Religious Sisters’ Identity Construction: A Study of Intersubjective Exchange in Religious Community Living

Abstract: Catholic religious sisters live community life in which they encounter communal relationship with each other, intertwined with power relations and dominance. The religious community context provides the sisters with on-going dialogical relationships laden with the discourse of religious obedience and practices associated with diverse status of being "superior/formator", "senior/older sister", "final professed" or "temporary professed sister". Within this discourse and practice of the vow of religious obedience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…Prior literature revealed there is abundant ambiguity associated with educational advancement within African congregations of women religious (Nakitende, 2015;Phiri et al, 2015). Differences in educational attainment had previously been found to create harmful conflicts regarding obedience and submission within a congregation (Eze et al, 2016). In contrast, the participants of this study expressed humility, gratefulness, and understanding related to the educational opportunity allotted to them.…”
Section: Impact On Understanding Of Life As a Woman Religiousmentioning
confidence: 60%
See 1 more Smart Citation
“…Prior literature revealed there is abundant ambiguity associated with educational advancement within African congregations of women religious (Nakitende, 2015;Phiri et al, 2015). Differences in educational attainment had previously been found to create harmful conflicts regarding obedience and submission within a congregation (Eze et al, 2016). In contrast, the participants of this study expressed humility, gratefulness, and understanding related to the educational opportunity allotted to them.…”
Section: Impact On Understanding Of Life As a Woman Religiousmentioning
confidence: 60%
“…Women religious are a part of a complex adaptive system, characterized by nonlinear local relationships and influenced by God, the Church, and their cultural context (Bircher & Hahn, 2016;Eidelson, 1997;Fidan & Balci, 2017). The complexity associated with the dynamic interactions of these agents can create some ambiguity for sisters in regard to their roles within the system (Eze et al, 2016). However, a servant leader values service above all else and achieves his or her own integrity through the service of others (Greenleaf, 1970).…”
Section: Impact On Understanding Of Life As a Woman Religiousmentioning
confidence: 99%
“…Así, no solo no presentan distinciones relevantes entre hermanas pertenecientes a distintas congregaciones, sino que tampoco aparecen diferencias en función de la edad o la nacionalidad, siendo la identidad de hermana religiosa un referente rector en la construcción de verdaderos estilos de vida, diluyendo la influencia de otras fuentes identitarias. Estos hallazgos son sintónicos con lo que refiere la literatura revisada, abundando en el sentido en que la identidad que construyen las hermanas religiosas tampoco se distingue en atención a los países en los que desempeñan su rol (Eze et al, 2014y 2016bis, Beribe et al, 2021, Halevy, 2022.…”
Section: Discussionunclassified
“…En este sentido, Eze et al (2016) reporta en su investigación autodefiniciones del yo basadas en cómo las construyen los demás, especialmente desde las posiciones de la jerarquía religiosa, y que tenderían a presentarse como aspectos integrales de la identidad personal/religiosa de las hermanas religiosas. Esta autora señala que tal influencia tributaría al principio de obediencia, en el entendido que la autoridad de la jerarquía derivaría de la autoridad de Dios, destacando la importancia de una conformación identitaria construida a partir de experiencias de socialización intensivas y significativas.…”
Section: Conclusiónunclassified
“…This is supported by various studies on practical issues that affected Consecrated Women in their community living (Van Deusen, 2009; Nyawira et al, 1998; Okure, 2010; Eze, Lindegger & Rakoczy, 2016). As a result, the researchers reported that religious communities' structures seemed designed to make adults keep acting like children (Eze et al, 2016). This is why this study is considered important and assumed to be a useful tool to help CWR in their journey towards integration and homeliness.…”
Section: Introductionmentioning
confidence: 91%